Multidisciplinary Consideration of Potential Pathophysiologic Mechanisms of Paradoxical Erythema with Topical Brimonidine Therapy. Issue 11 (November 2016) - Docherty, James; Steinhoff, Martin; Lorton, Dianne; Detmar, Michael; Schäfer, Gregor; Holmes, Anna; Nardo, Anna
Abstract Rosacea is a chronic inflammatory disease with transient and non-transient redness as key characteristics. Brimonidine is a selective α2-adrenergic receptor (AR) agonist approved for persistent facial erythema of rosacea based on significant efficacy and good safety data. The majority of patients treated with brimonidine report a benefit; however, there have been sporadic reports of worsening erythema after the initial response. A group of dermatologists, receptor physiology, and neuroimmunology scientists met to explore potential mechanisms contributing to side effects as well as differences in efficacy. We propose the following could contribute to erythema after application: (1) local inflammation and perivascular inflammatory cells with abnormally functioning ARs may lead to vasodilatation; (2) abnormal saturation and cells expressing different AR subtypes with varying ligand affinity; (3) barrier dysfunction and increased skin concentrations of brimonidine with increased actions at endothelial and presynaptic receptors, resulting in increased vasodilation; and (4) genetic predisposition and receptor polymorphism(s) leading to different smooth muscle responses. Approximately 80% of patients treated with brimonidine experience a significant improvement without erythema worsening as an adverse event. Attention to optimizing skin barrier function, setting patient expectations, and strategies to minimize potential problems may possibly reduce further the number of patients who experience side effects. Funding : Galderma International S.A.S., Paris, France.